'I could have used a lot more help...': The Impact of Australian Housing Market Dynamics upon Young Care Leavers and Homeless Youth. - Liddiard, Mark; Thoresen, Stian (SOAC: Causal Productions, 2011)
This paper draws upon the findings of two empirical research studies examining how the dynamics of a vibrant Australian housing market impact upon young people’s housing and often lead to homelessness for the most vulnerable, particularly care leavers. Largely excluded from home ownership; ineligible for social housing and forced to rely upon a highly competitive private rental market, many Australian young people find themselves experiencing significant difficulties with securing and maintaining independent housing. For some, their first experience of independence is homelessness, especially for young people leaving the purview of state care. Crucially, the dynamics of the housing market also impact heavily upon agencies working to support young people in their transition to independence, not least by limiting exit strategies and options for suitable move on accommodation. Drawing upon original interviews with support agencies and young care leavers, this paper raises some pertinent questions for policy makers and emphasises the importance of affordability problems for severely limiting the ability of many young people to both obtain and maintain independent housing. However, this paper also argues that housing and labour market dynamics should not be considered in isolation. On the contrary, it is clear that sometimes relatively small modifications to intervention and support for vulnerable young people can make a huge difference to their accommodation options and successful transitions from care or youth services to independent housing.